Management of intracranial hypertension: Recent advances and future directions - Shrestha, Gentle S; Pradhan, Saurabh (Bangladesh Critical Care Journal, 2017)
Intracranial hypertension is a major cause of morbidity and mortality in critically ill patients. Great deal of research has been done with the goal to improve patient outcome, but the challenges are enormous. From basic managementlike sedation and analgesia, to higher tier therapies, there are mixed evidences, some indicating these interventions to be beneficial and some to be equivocal, but the paucity of high-quality trials limits strong recommendations. This review will try to analyze the extensive literature regarding management of raised intracranial pressure, with particular focus on recent advances and will also try to shed some light on future directions. Bangladesh Crit Care J March 2017; 5(1): 53-62